Paying Off Debt or Forgiving Debt? Semantic and Intertextual Analysis on Lord’s Prayer in Smith-Van Dyck Arabic Bible Translation - Yuangga Kurnia Yahya; Siti Nikmatul Rochma; Umi Mahmudah (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2024)
The Smith and Van Dyck Arabic Bible Translation, which first appeared in 1865, is the most widely used translation in the Christian Arab community. The expressions that appear in the translation have some quite striking differences with other Arabic translations of the Bible. This research will focus on one of the messages in Lord's Prayer, specifically Matthew 6:12 about prayer for forgiveness and forgiveness to others which has different diction from the Jesuit Arabic Bible of 1881. This study will use a post-colonialism perspective in Bible studies through semantic and intertextual analysis. This research concluded two main things. First, the quality of the SVD Bible translation from English to Arabic, as seen in Matthew 6:12 has a low level of accuracy and legibility. This can be seen from the choice of words